The Role of City Design Elements in Tourist Villages as Interpreted by Online Media - Theodora, Aurelia Silviana; Julyanto, Pamela Felita; Novita, Adelia Tio; Kartika, Larasati Putri; Ekomadyo, Agus Suharjono; Susanto, Vanessa (University of Merdeka Malang, 2021)
In recent years, there have been numerous slum settlements in Indonesia that were transformed into tourist villages established by creative movements with an artistic approach. As a prominent aspect of the Penta helix, online media is considered a fundamental role in publicizing creative campaigns. This research utilizes the content analysis method to know how a designated space surfaces from a creative movement - the urban design elements of a tourist villageâ€™s inauguration, visualized by the media. Analysis of three tourist villages reveals two distinct patterns of tourist village coverage by the media: attractive city design elements that encourage social activities (Kampung Dago Pojok) and the unique form and massing as its picturesque appeal (Kampung Warna-Warni & Kampung Pelangi). Observational data shows that the internet has influenced the fabrication of tourist villages supported by creative movements with various urban design approaches.Â DOI:Â https://doi.org/10.26905/lw.v13i1.5129